Successful Treatment of an Infant with Left Ventricular Noncompaction Presenting with Fatal Ventricular Arrhythmia Treated with Cardiac Resynchronization Therapy and an Implantable Cardioverter Defibrillator - Masato Kimura; Kengo Kawano; Hisao Yaoita; Shigeo Kure (Case Reports in Cardiology)
We herein report the successful treatment of a 4-year-old girl with left ventricular noncompaction (LVNC) who presented with incessant ventricular fibrillation at 5 months of age. An implantable cardioverter defibrillator (ICD) was implanted, and dual chamber (DDD) pacing was initiated at 7 months of age. At her 10-month follow-up, her left ventricular ejection fraction (LVEF) had decreased from 45% to 20% with mechanical dyssynchrony. After upgrading to cardiac resynchronization therapy (CRT), the LVEF improved to 50%. The usefulness of CRT in pediatric LVNC has not been fully elucidated. However, our case suggests that CRT therapy may be an effective option for LVNC-induced cardiac dysfunction.